Impactos das relações interfirmas no desempenho das atividades de marketing - Kuhsler, Carolina (Universidade do Vale do Rio dos Sinos, 2014)
The transition from mass production to flexible production is considered the first and most widespread trend of organizational evolution. Hierarchical and bureaucratic structures dissipated, being replaced by new organizational forms, encompassing interfirm and interfunctional relationships. This phenomenon is considered a organizational strategic response to the environmental pressures and turbulence, which were incited to delegate its functions to other experts, through the establishment of interfirm relations. Moreover, theoretical studies suggested these relations could provoke higher marketing and organizational performance. In this context, this study investigated the interfirm relations impact over marketing and organizational performance, through a survey conducted with a sample of 464 organization. A scale to measure the frequency of establishment of interfirm relations was created and validated. The measurement of this construct was subsequently compared to marketing and organizational performance, which were also measured from existing scales in previous studies, which have been translated and validated. As main findings of the research, there is support to theoretical assumptions mentioned in the literature about marketing and organizational performance, the identification of marketing activities that interfere on marketing and organizational performance and the marketing activities more often performed from interfirm relationships.
Keywords: Interfirm Relation; Marketing performance; Organizational Performance; Adaptability; Effectiveness; Efficiency; Marketing activities; Relações interfirmas; Desempenho de marketing; Desempenho organizacional; Adaptabilidade; Eficácia; Eficiência; Atividades de Marketing; ACCNPQ::Ciências Sociais Aplicadas::Administração